SISTEM INFORMASI PENYEDIA JASA LAYANAN KOS (E-KOST) BERBASIS WEB (STUDI KASUS DI SEKITAR UNIKAMA) - Wali, Ananias; Agustina, Rini; Seby Dwanoko, Yoyok (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2025)
Students often face various complaints in finding boarding houses, ranging from unaffordable prices and limited availability to less than ideal boarding house conditions and locations far from campus or public facilities. Meanwhile, as a boarding house owner, it is also not easy to market boarding houses to compete with other boarding houses that may have lower operating costs or more modern facilities. The purpose of this research is to develop a web-based information system that provides complete information about boarding houses, as well as increasing efficiency and effectiveness in promoting and managing boarding houses. In the context of software development, the Waterfall method has proven to be one of the structured and systematic approaches. This method follows the following stages: Requirement Analysis and Definition, System and Software Design, Implementation and unit testing, Integration and System Testing, and Operation and Maintenance. The end result of each stage of this development is a system that is able to meet user needs to find boarding houses easily and quickly, and helps boarding house owners manage tenant and room data. This system has been designed with a user-friendly interface and is equipped with relevant features, such as searching by location, facilities, and price. This development process has also produced various findings and suggestions for future system development, such as integration with digital maps, mobile application development, and improving security features.